Digital Transformation as a Moderator: A Study of the Impacts of Sustainability Reporting Disclosure on Financial Reporting Quality in the Jordanian Banking Sector - Alroud Shaher Falah (ECONOMICS)
This study analyzes the impact of digital transformation on the relationship between sustainability reporting disclosure and financial reporting quality for Jordanian banks. Data were collected from Jordanian banks’ financial reports during the research period, spanning a couple of months, and questionnaires were administered to capture the financial reporting quality. Semi-structured interviews were also conducted with eight bank managers to obtain first-hand information concerning the role of digital transformation. With the use of multiple regression analysis, the study revealed that there is a statistically significant and positive relationship between sustainability reporting disclosure and quality of financial reporting with a coefficient of 0.042. Further, digital transformation was established to moderate this relationship with an effect size of 0.68, showcasing its crucial position in enhancing the nexus among sustainability practices and financial openness. Incorporating digital transformation into sustainability reporting practices has the potential to enhance financial reporting quality, operational effectiveness, and profitability. By enhancing digital competence and investing in staff and management capability, Jordanian banks are capable of aligning their sustainability targets with financial performance. This study contributes to the body of literature by way of emphasizing the moderating role of digital transformation in sustainability reporting and financial reporting quality, a less-researched area in emerging economies like Jordan. It offers practical guidance to policymakers and banking professionals on the imperative to adopt digital instruments for promoting sustainable and transparent financial operations. The results form the platform for follow-up research into how financial reporting, sustainability, and digital innovation combine in the case of banks.